Impact of mitral annular calcification associated mitral stenosis on clinical outcomes in patients undergoing transcatheter aortic valve implantation. (25th November 2020) - Mesnier, J; Urena, M; Nguyen, C; Carrasco, J.L; Terzian, Z; Fischer, Q; Brochet, E; Iung, I; Himbert, D
Abstract: Introduction: Mitral annular calcification (MAC) is a common finding in patient undergoing transaortic valve implantation (TAVI) and can cause significant mitral stenosis (MS). Purpose: To assess the impact of MAC associated with significant MS (MAC-MS) on clinical outcomes following TAVR. Methods: Consecutive patients undergoing TAVI in our institution between January 2008 and May 2018, were evaluated. All echocardiogram exams before intervention were analysed to identify the presence of MAC and MAC was confirmed on computed tomography (CT) scans. Patients were included in the MAC group if there was any calcification on the mitral annulus on CT scan. Severe MAC was considered as calcification of the mitral annulus involving over 50% of the circumference. Patients with a mitral mechanical valve or bioprosthesis and without CT scan available to confirm MAC were excluded (n=62). MAC-MS was defined as the association of MAC and a mean transmitral gradient over 5 mmHg. Results: Among 1177 consecutive finally included patients, 504 (42.8%) had MAC and 85 had a MAC-MS (7.2%, 16.9% among the MAC population). Compared to MAC without MS (MAC non-MS group) and non-MAC patients, patients with MAC-MS were more frequently women (p<0.0001), had a greater BMI (p=0.002), more previous pacemaker implantation (p=0.035), smaller indexed aortic valve area and left ventricular end systolic diameter (p=0.019 and p=0.038). At 30-days after TAVR, there were no differences in stroke, major vascular complication and pacemaker implantation between groups. However, MAC-MS patients had higher rates of tamponade [Odd Ratio adjusted 3.12, 95% confidence interval (CI) 1.08–9.07, p=0.036] and mortality [Adjusted hazard Ratio (HRa) 2.83, 95% CI 1.39–5.76, p<0.005] after adjustment on baseline characteristics. At 1 year, patients with MAC-MS had a higher risk of death [19 (22.1%) vs. 142 (13%); HRa 1.83, 95% CI 1.14–3.03, p=0.01] compared to MAC non-MS and non-MAC patients. Severe MAC was not a predictor of 1 year mortality. Conclusions: Mitral stenosis due to mitral annular calcification is infrequent in patient undergoing TAVI but is associated with higher early and mid-term mortality. Funding Acknowledgement: Type of funding source: None